An Interview with Peter Jaszi, Professor of Law, Faculty Director of the Glushko-Samuelson Intellectual Property Clinic - Taylor, Tucker; Myers, Carla S.; Wesolek, Andrew (Journal of Copyright in Education & Librarianship, 2018)
Peter Jaszi, copyright expert, lawyer, professor and author, was interviewed by the editors of the Journal of Copyright in Education and Librarainship on his carreer, influences, and copyright law, including what the future may hold for libraries and copyright. He also discusses the Codes of Best Practices for Fair Use, and gives advice for librarians who work with copyright.